Inseparable desire between women in literature - Donoghue, Emma 1969- (New York Alfred A. Knopf, 2010)
Explores the little-known literary tradition of love between women in Western literature, from Chaucer and Shakespeare to Charlotte Bronte?, Dickens, Agatha Christie, and many more. Donoghue examines how desire between women in English literature has been portrayed, from schoolgirls and vampires to runaway wives, from cross-dressing knights to contemporary murder stories. She writes about the half-dozen contrasting girl-girl plots that have been retold throughout the centuries; explores the writings of Sade, Diderot, Balzac, Thomas Hardy, H. Rider Haggard, Elizabeth Bowen and others and the ways in which the woman who desires women has been cast as not quite human, as ghost or vampire; she writes about the ever-present triangle, in which a woman and a man compete for the heroine's love, and about how and why same-sex attraction is surprisingly ubiquitous in crime fiction, from the work of Wilkie Collins and Dorothy L. Sayers to that of P.D. James. Finally she examines the plotline that has dominated writings about desire between women since the late nineteenth century: how a woman's life is turned upside down by the realization that she desires another woman, showing how this narrative pattern has remained popular and how it has taken many forms--From publisher description.
Travesties : The female bridegroom ; The male Amazon -- Inseparables : Shall we be sunder'd? ; Jealousies -- Rivals : Rakes vs. ladies ; Feminists vs. husbands ; The beautiful house -- Monsters : Sex fiends ; Secret enemies ; Not quite human -- Detection : Now you see it ; Crimes of passion ; It takes one to know one -- Out : Case histories ; On trial ; First love ; Devil may care ; Places for us.
UCWS-2014-G-1669 donated by Dr. Rommel Sta Ana
Keywords: English literature -- History and criticism; French literature -- History and criticism; Lesbianism in literature; Desire in literature; Women in literature